The Concept of “World Order”: Theories and Reality - B. I. Nefedov (Сравнительная политика, 2021)
At present, there is no common perception in modern science and international political practice of what the world (international) order (legal order) is. The article analyzes the relevant points of view. It is concluded that by referring to the relevant provisions, generally accepted in the framework of the general theory of law and the theory of international law, it is possible to get close enough to the solution of this problem. The article also examines other problems related to the essence of the concepts of the world (international) order and its types (world public order, world legal order and global world legal order), and also the varieties of social norms of the international regulatory system, the results of the implementation of which shape the corresponding orders. Special attention is paid to the fact that, in contrast to the widespread perceptions, all three types of world order are neither a set of international relations, nor a set of norms regulating such relations. According to the theory of international law, they are the result of the implementation of the requirements of certain norms of the international regulatory system aimed at managing international public relations. In addition, various factors inﬂuence the state of a particular type of international order (including a change in the hierarchy of states depending on their role in the international political and/or economic system, the formation of new centers of power, a change in bipolarity, polycentricity or monocentricity of the world, the emergence of multilateral integration formations, the activities of international multilateral institutions, etc.), but they should also not be confused with international orders themselves.